Storage of Information and Its Implications for Human Development: A Dialectic Approach - Zlotnik, Gregorio; Vansintjan, Aaron (Frontiers in Psychology, 2020)
How has the storage of information shaped human cognition? We bring together current advances in cognitive science, the neurobiology of memory, and archaeology to explore how storage of information affects consciousness. These fields strongly suggest that the increase in storage of information in the environment – which we call exosomatic storage of information – may have led to changes in human consciousness and human neurophysiology over time. To bring these findings together conceptually, we develop what we call a dialectical model of the relationship between storage of information and the development of human consciousness. Using the system of dialectic philosophy, we put forward that (a) environmental changes, consciousness, and neurophysiology develop together, (b) these changes were irreversible, (c) quantitative increases in exosomatic storage of information may have led to qualitative changes in human consciousness and neurophysiology, (d) these changes in turn affected how we see ourselves. Indeed, our capacity to store information exosomatically distinguishes us from other animals, and may be a key attribute of our self-awareness and therefore self-consciousness. Because metaphors are central to human thought and can help structure scientific inquiry, we illustrate our model using a metaphor of drops of silver on the back of a glass, eventually making a mirror—where successive quantitative change leads to an irreversible qualitative development in human consciousness. The dialectic model can offer new insights into the co-evolution of material culture and human beings through its broader philosophical foundations and explanatory power.